Implementasi Sapta Pesona dalam Pariwisata Raja Ampat - Mulyani, Dea Sri Mulyani; Fadjarajani, Siti; Darmawan, Cahya (Jurnal Abdimas Pariwisata, 2025)
Implementation of Sapta Pesona in Raja Ampat Tourism Raja Ampat as one of the most beautiful natural tourist destinations in the world, is known for its stunning coral reefs and marine biodiversity. To maintain the sustainability of this destination, the Sapta Pesona Concept is implemented, which includes safety, orderliness, cleanliness, coolness, beauty, friendliness, and memorable experiences as government policies. This study aims to examine the implementation of Sapta Pesona in the management of tourism in Raja Ampat and evaluate its impact on the quality of the destination and the tourist experience. Using a descriptive qualitative approach through literature review, the results show that the implementation of Sapta Pesona in Raja Ampat has successfully improved the quality of the tourist destination and maintained environmental sustainability.